Navigating Genre-based Writing Model for Academic Purposes - Hasyim, Nur (International Journal of Psychosocial Rehabilitation, 2020)
Genre in the research world tend to use distinct from the other context of situation. Genre in academic writing can be called as culture-based specific argument styles due to its logical reasoning, and organizational patterns in their writings. The competency in academic writing are not only based on linguistic ability but also on awareness of linguistics feature of writing accepted by discourse community. This paper is a report of the third year of three-year-research scheme funded by Research Division of Jakarta State Polytechnic. This particular research objective is to develop a genre-based writing model for Applied Master Thesis especially for Applied Master students and generally for the others who want to make final project for his or her writing. The model was the configuration of Martin‟s (1992) and Martin and Rose‟s (2006), Halliday and Hassan] (1985), and Swales] (1990) concept of genres and the result of content analyses of applied master students‟ writing model covering part to part of the text until the whole part of the text, on the other hands. The embryo model was discussed with the SFL experts, the applied master lecturers in State Polytechnic of Jakarta, and applied master students in State Polytechnic of Jakarta. The model was later tested to the applied master students in State Polytechnic of Jakarta. The test is used to find out whether the training and the model are effective to achieve the more appropriate writing the discourse or text. The results showed that there are at least five factual genres which is recommended to use in writing applied master theses. The factual genres are descriptive, report, discussion, procedure, exploration.